Genome-wide identification and functional validation of sterol C-22 desaturases and C-24 methyltransferases in Asparagus officinalis and Asparagus taliensis - Brown, Sylvia E.; Li, Yunbin; Lin, Chun; Liu, Zhengjie; Mao, Zichao (Frontiers in Plant Science, 2025)
IntroductionSteroids are essential components of plant membranes and serve as precursors of brassinosteroids (BRs) and Steroidal saponins (SSs), which regulate growth, development and stress adaptation. Sterol-modifying enzymes, including C-22 desaturases (C22SDs) and C-24 methyltransferases (C24SMTs), act as key branch-point regulators of side-chain remodeling, yet their molecular roles in Asparagus remain poorly characterized.MethodsFunctional genomics analysis of C22SD and C24SMT families was conducted in Asparagus officinalis and A. taliensis, integrating genome-wide identification, phylogenetic reconstruction, gene structure, conserved motif and cis-element analyses. Transcriptomics-based expression profiling revealed tissue-specific expression patterns, supporting functional divergence among gene family members. Structural modeling and molecular docking highlighted conservation of catalytic residues and predicted substrate interactions.ResultsTo overcome transformation barriers in Asparagus, functional validation was performed in Neurospora crassa, where targeted disruption of erg5, erg6 or both impaired ergosterol biosynthesis, growth and membrane fluidity, while complementation with selected Asparagus genes restored these traits. The results catalog C22SD/C24SMT families and show heterologous complementation of Δerg5, Δerg6 and Δerg5/Δerg6 mutants in N. crassa, indicating catalytic competence in eukaryotic sterol pathway, in-planta roles remain to be established.DiscussionBy characterizing sterol side-chain remodeling enzymes, this study establishes a framework for understanding the potential roles of these enzymes in membrane stability, hormone biosynthesis and defense metabolite production, with implications for stress resilience and metabolic engineering. These findings highlight sterol remodeling as a potential target for developing stress-resilient crops.